Design of Differentiated PAI Learning Through a Scaffolding Approach with Student Worksheet Media to Improve Student’s Understanding - Is'ad Ummul Choiriyah; Dafina Ainani Zahra; Asep Saepul Hamdani; Is'ad Churiyah Zahidah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This research is motivated by the fact that Islamic Religious Education (PAI) learning is still uniform, thus not accommodating the differences in student abilities. The purpose of this study was to design and analyze the implementation of differentiated learning through a scaffolding approach using Student Worksheets (LKPD) to improve student understanding and learning independence. The method used was descriptive qualitative, with data collection techniques through literature review, observation, and analysis of LKPD draft documents. The results show that the combination of differentiation and scaffolding in LKPD can accommodate student diversity, increase learning engagement, and encourage the development of religious character. Each LKPD is designed with different levels of support according to student abilities—beginner, developing, and advanced—so that the learning process progresses gradually toward independence. In conclusion, this model is effective in improving understanding of Islamic values and is relevant to the principles of the Independent Curriculum. This research contributes to the development of a humanistic, adaptive, and contextual PAI curriculum.